'Neither a borrower nor a lender be': Letters from the anaesthetist Joseph Thomas Clover to the Birmingham surgeon Joseph Sampson Gamgee. (February 2019) - Ball, Christine M
The London surgeon and anaesthetist, Joseph Thomas Clover (1825–1882), and the Birmingham surgeon, Joseph Sampson Gamgee (1828–1886), are well known figures in the history of medicine. Draft letters among the surviving papers of Joseph Clover have been transcribed and reveal new information about their friendship, their financial affairs and Clover's motivation to become a full-time anaesthetist. They have also led to the discovery that Gamgee was briefly imprisoned in Warwick County Goal for debt in 1859.